Integration of Local Cultural Values in Forming Student Morale in Learning Islamic Religious Education in Junior High Schools - Maideja, Fika; Sukri, Ahmad; Sari, Irva Rahma; Maideja, Fiki; Illahi, Tri Fahmi Nova Wahyu (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2023)
This study aims to analyze how local (Minangkabau) cultural integration forms in learning Islamic religious education, and its effect on the behavior of students in secondary schools. This study used a qualitative method with a case study approach, data were collected through in-depth interviews with ten informants consisting of school principals, Islamic religious education teachers, culture and arts teachers and students. All data were analyzed using the Miles and Huberman technique. The research findings show four forms of integration of local (Minangkabau) culture with the learning of Islamic religious education conducted by the school. The four integrations are (cultural learning through Islamic religious education subject matter, holding traditional dress days at school, shaping the daily behavior of students according to culture, holding extracurricular activities about cultural and customary teachings. Furthermore, the findings also found that the integration of local (Minangkabau) culture with Islamic religious education has an effect on the attitudes and behavior of students such as (ability to communicate well, growing attitudes of loving culture and customs, liking to dress in traditional clothes that are more polite and neat). This integration model can be used as a reference for other schools in teaching values culture and customs through learning Islamic religious education